Influence of soot on tribological performance of uncoated and DLC-coated lubricated contacts. Friction and wear analysis. - Hyla, Edona (2019)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia